Reducing Chemical Oxygen Demand and Turbidity Levels in Laundry Waste Using Activated Carbon from Water Hyacinth Leaves - Cucun Alep Riyanto; Nur Ayu Hidayati; Yohanes Martono (Indonesian Journal of Chemical Analysis (IJCA), 2023)
Lignocellulose compounds contained in water hyacinth leaves (WHL) (Eichhornia crassipes) can be used as raw material for the manufacture of activated carbon at a low and renewable rate. The ACWHL can be used as adsorbent for reducing a COD value and turbidity levels on laundry waste. The purpose of this study is to determine the best adsorption modelling of ACWHL on COD values and turbidity levels in laundry waste in kinetics and isotherm studies and determine the effectiveness of reducing a COD value and turbidity levels. The process of making ACWHL is carried out by carbonization at 400 Â°C for 1 hour, then activated using 30% H3PO4 at an impregnation ratio of 1:4 (w/w) for 24 hours and physical activation at 600 Â°C for 1 hour. The results showed that the adsorption of ACWHL on COD value and turbidity levels of laundry waste followed Freundlich isotherm and Elovich isotherm modelling with R2 values of 0.9535 and 0.9905, respectively. The modelling for adsorption kinetics of COD values and turbidity levels in laundry waste follows the Pseudo Second Order kinetics modelling. The effectiveness of ACWHL reduction in adsorption of COD value and turbidity levels of laundry waste was 80.76% and 64.71%.